Experiences With Online Teaching and Psychological Adjustment of High-School Students at the Onset of the COVID-19 Pandemic in Croatia - Buško, Vesna; Bezinović, Petar (Frontiers in Psychology, 2021)
Vastly changed schooling surroundings due to COVID-19 crisis have generally limited the opportunities and resources for schools to provide necessary psychological and other support to their students. In such circumstances, educators and all involved in the schooling system need to understand the kinds of students’ experiences with distance learning and how they adapt to novel life and studying conditions. The study aims to examine what are the relevant sources of stress students encounter with regard to online classes and frustrations due to living in social isolation, as well as how these stressors relate to the measures of emotional wellbeing and psychological adjustment of students. The data were collected in April 2020 via an online questionnaire administered on a sample of 4.492 students (62,6% of females) attending all four grades of high-schools within two Croatian counties. The results point to differential effects of particular aspects of online teaching practices on the stressful experiences of students. Furthermore, the results of MANOVA and canonical discriminant analyses demonstrated statistically and practically notable gender and grade differences in the structure of emotional and behavioral adaptation of students to the health crisis. Thus, female students and predominantly those attending the highest grades reported higher frequency and intensity of short-term emotional and psychosomatic difficulties. Alternatively, male students of the final grade scored highest on the dimension defined by the extensity of online teaching stressors. The obtained results are interesting in view of hypothetical accounts of adjustment mechanisms based on existing stress theories. Moreover, the findings serve as a basis for teachers’ self-reflection and self-evaluation of schools which is then expected to lead to designing specific programs of support in learning and adaptation to the new living and studying conditions.